Pengaruh Cash Holding, Nilai Perusahaan, dan Leverage terhadap Income Smoothing dengan Ukuran Perusahaan sebagai Variabel Moderasi - Dinda Agustin; Ela Widasari; Firda Mufidah (Politeknik Ganesha Medan, 2026)
This study aims to analyze the effect of cash holdings, firm value, and leverage on income smoothing, with firm size as a moderating variable in the property and real estate sector listed on the Indonesia Stock Exchange for the 2020–2024 period. The study employed a quantitative approach with purposive sampling, resulting in 34 companies with a total of 170 observations. Data analysis was conducted using logistic regression and Moderated Regression Analysis (MRA). The results showed that cash holdings had a positive and significant effect on income smoothing, while leverage had a negative and significant effect on income smoothing. Meanwhile, firm value, proxied by Price to Book Value (PBV), did not have a significant effect on income smoothing. Moderation testing showed that firm size moderated the relationship between cash holdings and leverage on income smoothing, but not the relationship between firm value and income smoothing. These findings indicate that post-pandemic conditions in the property sector have led to liquidity pressures and creditor oversight becoming important factors influencing management behavior in implementing income smoothing practices. This study contributes to the development of literature related to the determinants of income smoothing in the property and real estate sector in Indonesia.